Host–guest architectures with a surface confined imine covalent organic framework as two-dimensional host networks. Issue 56 (22nd June 2016) - Sun, Jiang; Zhou, Xin; Lei, Shengbin
Abstract : Surface COF is used as a host to accommodate three guest molecules, and selective accommodation of F16 CuPc was confirmed by STM and DFT investigation. Abstract : A two-dimensional covalent organic framework (2D COF), synthesized on a highly oriented pyrolytic graphite (HOPG) surface with benzene-1, 3, 5-tricarbaldehyde and p -phenylenediamine as the precursors, is used as a host to accommodate three guest molecules, coronene, copper phthalocyanine (CuPc), and fluorine-substituted copper phthalocyanine (F16 CuPc). The host–guest interaction and dynamic behavior were investigated by scanning tunneling microscopy and density functional theory.